2014
DOI: 10.1007/s10072-014-1750-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender and triptan efficacy: a pooled analysis of three double-blind, randomized, crossover, multicenter, Italian studies comparing frovatriptan vs. other triptans

Abstract: Migraine is three times as common in females as in males, and attacks may be more severe and difficult to treat in women. However, no study specifically addressed possible gender differences in response to antimigraine therapy. The objective of this study was to review the efficacy of frovatriptan vs. other triptans, in the acute treatment of migraine in subgroups of subjects classified according to gender (men vs. women) through a pooled analysis of three individual randomized Italian studies. 414 patients su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
(35 reference statements)
1
21
0
Order By: Relevance
“…Regarding the lack of association between sex and migraine outcomes, we identified similar data from the outpatient setting. In a post hoc analysis of pharmaceutical data, men and women demonstrated comparable rates of short‐term and sustained headache relief after oral triptans . However, other investigators reported that women experience migraine recurrence after successful treatment with oral triptans more frequently than men .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Regarding the lack of association between sex and migraine outcomes, we identified similar data from the outpatient setting. In a post hoc analysis of pharmaceutical data, men and women demonstrated comparable rates of short‐term and sustained headache relief after oral triptans . However, other investigators reported that women experience migraine recurrence after successful treatment with oral triptans more frequently than men .…”
Section: Discussionmentioning
confidence: 96%
“…In a post hoc analysis of pharmaceutical data, men and women demonstrated comparable rates of short-term and sustained headache relief after oral triptans. 18 However, other investigators reported that women experience migraine recurrence after successful treatment with oral triptans more frequently than men. 19,20 We were not able to replicate this latter finding in our analysis of sustained headache response, which incorporates the potential for headache recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear what, if any, relationship exists between the efficacy of these agents in migraine and the plasma concentration achieved (Ferrari et al, 2011;Vetvik and Macgregor, 2017). However, in comparison trials of frovatriptan versus rizatriptan, zolmitriptan, or almotriptan, all produced relatively similar efficacy to ameliorate or eliminate migraine headache, which was not different when men and women were compared (Franconi et al, 2014). A recent metaanalysis did, however, find an increased risk for women to have headache reoccurrence 24 and 48 h after triptan treatment, and concluded that this was not explained by a different initial response to these abortive drugs (van Casteren et al, 2019).…”
Section: Triptansmentioning
confidence: 99%
“…European studies have shown higher MIDAS scores and higher disability in women, but sex differences in the individual criteria have not been reported [17,45,46,47].…”
Section: Specific Disabilitiesmentioning
confidence: 91%
“…However the most constant finding is that women report longer duration of migraine attacks than men [17]. Some clinical forms are well described as catamenial migraine.…”
Section: Clinical Featuresmentioning
confidence: 99%